QKD protected fiber-based infrastructure for time dissemination - Alice Meda; Alberto Mura; Salvatore Virzì; Alessio Avella; Filippo Levi; Ivo Pietro Degiovanni; Andrea Geraldi; Mauro Valeri; Silvia Di Bartolo; Tommaso Catuogno; Mattia Verducci; Marco Genovese; et al. (Scientific Reports)
Abstract In this study, we demonstrate the possibility to protect, with Quantum Key Distribution (QKD), a critical infrastructure as the fiber-based one used for time and frequency (TF) dissemination service. The proposed technique allows to disseminate secure and precise TF signals between two fiber-optic-connected locations, on a critical infrastructure, using both QKD and White Rabbit technique. This secure exchange enables the secret sharing of time information between two parties, allowing the synchronization of distant clocks with a stability of $$10^{-10}$$ at 1 s, traceable to the Italian time scale. When encrypted, the time signals provide no useful information to a third party regarding the synchronization status, resulting in a time stability degraded by two orders of magnitude.